Fuzzy Graph–Based Encryption using Special Characters - S. Dharani; K. Jency Priya; B. Amala Jasmine; V. Vanitha; T. Sathinathan (The Bioscan, 2026)
This work presents a novel data encryption method using fuzzy graph theory. The plaintext is represented as a fuzzy graph, where characters act as vertices with membership values and their relationships form fuzzy edges. The encryption process uses two secret keys to introduce uncertainty within the interval [0,1].Different models are developed for handling alphabets, numbers and special characters. A systematic decryption process ensures accurate recovery of the original message. This approach enhances data security by making the encrypted information difficult for unauthorized users to interpret, while maintaining flexibility and efficiency.